Environmental effect of pollution and smoking on protein, cholesterol, albumin and bilirubin - Iqbal, Zafar; Bangash, A. H.; Zakir, S.; Ullah, Ihsan; Rasheed, H. (The Nucleus, 2020)
In order to see the effect of pollution and smoking, blood samples of 153 healthy adult men volunteers were collected from polluted and non-polluted areas of Peshawar. The age, height, duration and stay in the specific area and smoking habits were recorded. Serum was analyzed for protein, cholesterol, albumin and bilirubin. The data revealed that pollution and smoking both have no significant effect on the level of cholesterol while smoking has prominent effect on the level of total protein. The results show that pollution has a prominent effect on serum albumin i.e. the level of serum albumin was higher in smoker living in non-polluted area compared to the polluted area. From the observations, it is clear that pollution has altered the level of bilirubin and significant difference was observed in smokers and non-smokers living in polluted and non-polluted area. The data also indicate that the level of bilirubin was higher in volunteers living in non-polluted area than polluted area.